QUALITY CONTROL OF TWO HERBAL ACTIVE INGREDIENTS FROM LOCAL PRODUCTION CENTERS, VILLA CLARA - Portela García, Glenda; Bofil Morrell, Isela; Jorge Rodríguez, María Elisa; Saucedo Hernández, Yanelis; Pedraza Beltrán, Madiley; Ramos Hernández, Ismarys (Centro Azúcar Journal, 2024)
Introduction: The leaves of Plectranthus amboinicus (Lour.) Spreng, commonly known as French oregano, are traditionally used for their action as an anti-asthmatic, expectorant, bronchodilator and antimicrobial, while the bark of Citrus sinensis L. is used as an anti-inflammatory, antitussive and expectorant. Objective: To verify specifications for quality control of herbal active ingredients obtained from P. amboinicus and C. sinensis powder. Materials and Methods: In this study, the quality control of ten lots supplied by the laboratories of different municipalities in the province of Villa Clara was carried out, applying tests described in pharmacopoeias BP (2020), UPS (2017) and in the national formulary. Results and Discussion: The results revealed that the loss on drying should not exceed 11%, while the total ashes should not be greater than 20 and 7% and the ashes insoluble in hydrochloric acid should not exceed 8 and 2% for oregano and peel orange, respectively. Thin layer demonstrated the presence of carvacrol in French oregano and quercetin and hesperidin in orange peel. The leaves of Plectranthus amboinicus contain not less than 0.7% carvacrol and the peel of Citrus sinensis contains not less than 0.2% flavonoids; these metabolites provide the pharmacological actions for which both plants are used in Cuban traditional medicine. Conclusions: Both raw materials have adequate quality by complying with the quality specification limits of the tests evaluated in this work.